Calculations of extreme sea level rise scenarios are strongly dependent on ice sheet model resolution - C. Rosie Williams; Pierre Thodoroff; Robert J. Arthern; James Byrne; J. Scott Hosking; Markus Kaiser; Neil D. Lawrence; Ieva Kazlauskaite (Communications Earth & Environment)
Abstract The West Antarctic Ice Sheet (WAIS) is losing ice and its annual contribution to sea level is increasing. The future behaviour of WAIS will impact societies worldwide, yet deep uncertainty remains in the expected rate of ice loss. High-impact low-likelihood scenarios of sea-level rise are needed by risk-averse stakeholders but are particularly difficult to constrain. Here, we combine traditional model simulations of the Amundsen Sea sector of WAIS with Gaussian process emulation to show that ice-sheet models capable of resolving kilometre-scale basal topography will be needed to assess the probability of extreme scenarios of sea-level rise. This resolution exceeds many state-of-the-art continent-scale simulations. Our ice-sheet model simulations show that coarser resolutions tend to project a larger range of sea-level contributions than finer resolutions, inflating the tails of the distribution. We therefore caution against relying purely upon simulations 5 km or coarser when assessing the potential for societally important high-impact sea-level rise.